Supplement Book of Social Studies Teaching Materials Through the Empowerment of Bali Local Wisdom as A Learning Source - I Wayan Kertih; I Putu Sriartha (Jurnal Pendidikan dan Pengajaran, 2022)
The problem is, ideologically, social studies education that has been carried out so far is more oriented towards state political nationalism and the domination of local ideologies, including the local ideology of the Balinese people. This research aims to develop a Supplementary Book of Social Studies Teaching Materials through the empowerment of Balinese Local Wisdom as a Learning Resource at the SMP/SMP level. This research is designed as research development or Research and Development (R&D). This article is the product of the first year of research conducted to identify and analyze Balinese local wisdom needed as material for Balinese Local Wisdom Textbooks. This first-year research used a bibliographic research design. The object of study consists of curriculum documents; textbooks used by teachers of social studies subjects at junior high school through the empowerment of the local wisdom of the Balinese people. Data collection techniques are interviews, observation, documentation studies, and expert judgment. The data collected is in the form of qualitative data. Data processing using non-statistical analysis. The study results indicate that there are various forms and types of Balinese local wisdom that can be used and developed as material for Social Studies Textbooks at the Bali Local Wisdom Middle School.